Al-Khashaish al-Fanniyah fi Khutab al-Syaikh al-Syarif Ibrahim Shalih al-Husaini - Muhammad, Ibrahim Harun; Badr, Muhammad Abu Bakr (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
This article, entitled Some Artistic Characteristics of the Sermons of Sheikh Sharif Ibrahim Saleh Al-Husseini, aims to introduce the preacher, the sermon, and highlight the artistic characteristics of the sermons of this personality. Sheikh Ibrahim Saleh Al-Husseini is a figure of Nigerian Arabic literature and an eloquent preacher. He was born in a village in Nigeria. He accompanied scholars and traveled to many countries in the Islamic world, during which he met the leaders of the contemporary Islamic nation. He began preaching since he was young. Among the results that the researchers reached were: that the characteristics of his sermons were length, frequent citations of Quranic verses, ease of expression, commitment to the artistic structure of the sermon, and unity of subject